Stability and normal zone propagation in YBCO CORC cables. (11th March 2016) - Majoros, M; Sumption, M D; Collings, E W; van der Laan, D
Abstract: In this work, a two layer conductor on round core cable was tested for stability and normal zone propagation at 77 K in a liquid nitrogen bath. The cable was instrumented with voltage taps and wires on each strand over the cable's central portion (i.e. excluding the end connections of the cable with the outside world). A heater was placed in the central zone on the surface of the cable, which allowed pulses of various powers and durations to be generated. Shrinking (recovering) and expanding (not recovering) normal zones have been detected, as well as stationary zones which were in thermal equilibrium. Such stationary thermal equilibrium zones did not expand or contract, and hit a constant upper temperature while the heater current persisted; they are essentially a form of Stekly stability. Overall, the cable showed a high degree of stability. Notably, it was able to carry a current of 0.45 I c cable with maximum temperature of 123 K for one minute without damage.